Leading Sectors and Inequality in Urban Areas of DKI Jakarta Province - Taufiqqurrachman, Fahrizal (MediaTrend, 2025)
This study aims to find out the economic structure in 5 cities in DKI Jakarta Province. The research method uses descriptive quantitative research with data sources from the Central Statistics Agency. The 2 analysis tools used are Location Quotient (LQ) and Williamson Index (IW). The development process of DKI Jakarta Province has experienced obstacles due to the Covid-19 pandemic so that it has experienced economic recovery in 2021 post-pandemic. Location Quotient analysis shows that South Jakarta does not have a superior sector, West Jakarta and Central Jakarta have 1 superior sector while the most superior sectors are in North Jakarta with 6 sectors and East Jakarta with 7 sectors. The Williamson Index shows that 2 regions, namely West Jakarta and Central Jakarta, experienced a decrease in income inequality while North Jakarta, South Jakarta and East Jakarta experienced an increase in income inequality. Despite being faced with various problems in regional development in terms of sectoral and income inequality, DKI Jakarta is still a benchmark and reference for development for other regions.